HUBUNGAN PENGETAHUAN, SIKAP, PERILAKU KEPALA KELUARGA DENGAN PENGAMBILAN KEPUTUSAN PENGOBATAN TRADISIONAL DI DESA RAMBAH TENGAH HILIR KECAMATAN RAMBAH KABUPATEN ROKAN HULU, RIAU - Desni, Fitriana; Wibowo, Trisno Agung; Rosyidah, . (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2011)
Background: Indonesia has long recognized and uses traditional medicine as an effort in tackling health problems. Persons behavior in decision-making related to knowledge and attitude of a person in seeing a problem. The interviews found 30% of the population still believes in traditional medicine than medical treatment for about public trust traditional medicine, get counseling about medical treatment and health service facilities are difficult to reach. The purpose of this research is to know the relationship of knowledge, attitudes, behavior family heads with the traditional treatment decision-making in the village of Central Rambah Hilir, Rokan Hulu, Riau. Methods: This study was observational analytic research with cross sectional design. Population studies of the head of the family who are living in the village of Lower Central District Rambah Rokan Hulu in Riau. Sampling technique it was by random sampling to multistage sampling approach. Samples obtained as many as 86 people. Descriptive data analyzed using frequency distribution tables and analytically to determine the relationship between two variables with chi-square. Results: Result of research indicate that there was relation having a meaning amongh knowledge household with the decision making of traditional medicine equal to p=0,003. There was relation between of among attitude household and with the decision making of traditional medicine equal to p=0,000. There is relation having a meaning of among behavior household with occurrence of the decision making of traditional medicine equal to p=0,000. Conclusion: All accurate free variables there was relation between knowledge, attitudes, behavior and decision making of traditional medicine. Keywords: Knowledge, attitudes, behaviors, and traditional medical decision making.